531 AFM13-targeted blood and cord-blood-derived memory-like NK cells as therapy for CD30+ malignancies. (9th November 2020) - Kerbauy, Lucila; Marin, Nancy; Kaplan, Mecit; Banerjee, Pinaki; Berrien-Elliott, Melissa; Becker-Hapak, Michelle; Basar, Rafet; Foster, Mark; Melo, Luciana Garcia; Neal, Carly; McClain, Ethan; Daher, May; et al.
Abstract : Background: Natural killer (NK) cells are a nascent cellular immunotherapy for hematologic malignancies. Target recognition of NK cell-resistant cancers remains a substantial barrier to broad application of NK cell therapy. One solution are bispecific engagers that trigger NK cells via an NK activating receptor when simultaneously engaging a tumor-specific antigen. Methods: Here, we investigated single NK cell responses stimulated by the tetravalent bispecific innate cell engager (ICE®) AFM13 that binds CD30 on leukemia/lymphoma targets and CD16A on several types of NK cells. Results: Multidimensional mass cytometry revealed heterogeneity within AFM13-directed conventional (c)NK cell responses, as well as consistent polyfunctional activation of mature terminally differentiated NK cells across donors. The source of NK cells also impacted the AFM13 response, with cNK cells from healthy donors exhibiting superior responses to those from Hodgkin lymphoma patients. IL-12, IL-15, and IL-18-induced memory-like NK cells from peripheral blood exhibited enhanced killing of CD30+ lymphoma targets directed by AFM13, compared to cNK cells. Cord-blood expanded NK cells that were pre-activated with IL-12, IL-15 and IL-18 also exhibited enhanced killing with AFM13 stimulation, via upregulation of signaling pathways related to NK cell effector function. These cells were stably pre-loaded with AFM13 enhancing responses to CD30+ lymphomas in vitro and in vivo in immunodeficient NSG mouse models. Conclusions: Collectively, these data identify promising combinations of AFM13 with cytokine-activated adult blood or cord blood NK cells against CD30+ hematologic malignancies, warranting clinical trials with these novel combinations.